Cognitive Sphere and Neuroimaging Changes in Patients with Vascular Debt: Parallels and Correlations (Eurasian Medical Research Periodical, 2023)
Vascular dementia is not one disease, but several outlined syndromes, for which a common feature is the relationship between damage to the cerebral vessels and the development of symptoms of brain damage. Neuroimaging screening for COD involves magnetic resonance imaging (MRI) and a characteristic picture is the presence of leukoaraiosis. The aim of the study was to identify the presence of a parallel and correlation between the cognitive sphere and neuroimaging in patients with vascular dementia.